Research Progress on the Extraction and Purification of Anthocyanins and Their Interactions with Proteins - Hongkun Xue; Min Zha; Yingqi Tang; Jianduo Zhao; Xiaopeng Du; Yu Wang (Molecules, 2024)
Anthocyanins, as the most critical water-soluble pigments in nature, are widely present in roots, stems, leaves, flowers, fruits, and fruit peels. Many studies have indicated that anthocyanins exhibit various biological activities including antioxidant, anti-inflammatory, anti-tumor, hypoglycemic, vision protection, and anti-aging. Hence, anthocyanins are widely used in food, medicine, and cosmetics. The green and efficient extraction and purification of anthocyanins are an important prerequisite for their further development and utilization. However, the poor stability and low bioavailability of anthocyanins limit their application. Protein, one of the three essential nutrients for the human body, has good biocompatibility and biodegradability. Proteins are commonly used in food processing, but their functional properties need to be improved. Notably, anthocyanins can interact with proteins through covalent and non-covalent means during food processing, which can effectively improve the stability of anthocyanins and enhance their bioavailability. Moreover, the interactions between proteins and anthocyanins can also improve the functional characteristics and enhance the nutritional quality of proteins. Hence, this article systematically reviews the extraction and purification methods for anthocyanins. Moreover, this review also systematically summarizes the effect of the interactions between anthocyanins and proteins on the bioavailability of anthocyanins and their impact on protein properties. Furthermore, we also introduce the application of the interaction between anthocyanins and proteins. The findings can provide a theoretical reference for the application of anthocyanins and proteins in food deep processing.